Institutional Practices of Propaganda in Nicolae Ceauşescu’s Regime - PREUTU, Cristina (Studia Universitatis Babeș-Bolyai Historia, 2015)
The aim of this study is to analyse the link between the evolution of the Department of Propaganda and Agitation and the evolution of the internal and foreign policy in the Nicolae Ceausescu regime. Could the communist propaganda system be simply a bureaucratic construct that created an artificial speech? If not, what would be the connection between the institutional practices of propaganda and the evolution of the regime? In order to answer these questions I used, in particular, archival documents from The National Archives of Romania and the Central Committee of the Romanian Communist Party Fund from the Department of Propaganda and Agitation. My analysis follows two key moments related to the reorganizations of the Central Institution of Propaganda from the years 1968 and 1973. In this respect, I analyse the changes imposed on these institutions and their connection with the internal and the external context of the regime.